Device-based threading dislocation assessment in germanium hetero-epitaxy - Simoen, Eddy; Claeys, Cor; Oliveira, Alberto; Agopian, Paula [UNESP]; Martino, Joao; Hsu, Brent; Eneman, Geert; Rosseel, Eric; Loo, Roger; Arimura, Hiroaki; Horiguchi, Naoto; Wen, Wei-Chen; et al. (Institute of Electrical and Electronics Engineers (IEEE), 2019)
A review on the electrical activity of extended defects and, more specifically, threading dislocations in germanium hetero-epitaxial layers is reported here. Focus is on the impact of some basic types of devices, like a p-n junction diode, a Metal-Oxide-Semiconductor (MOS) capacitor and a Fin-Field-Effect Transistor (FinFET) fabricated in Ge-on-Si. A good understanding of the impact on the leakage current and lifetime in p-n diodes will be shown. Deep-Level Transient Spectroscopy on Ge MOScaps enables the investigation of bulk and interface states related to threading dislocations Finally, the application of Generation-Recombination (GR) noise spectroscopy to the study of GR centers in strained and relaxed Ge-on-Si FinFETs will be illustrated.
Keywords: Deep-Level Transient Spectroscopy; Extended Defects; FinFETs; Generation-Recombination noise; Germanium-on-silicon; leakage current; MOScap; p-n junction diode; Threading Dislocations